Coherence Function of Wind and Waves ofMetocean Data - Mohamad Nasir, Quailid Rezza (Universiti Teknologi Petronas, 2011)
In this paper, a research regarding analysis of metocean data is done that includes two main parameters; wind and waves. The objective of this project is mainly to apply Coherence Function as the mechanism tool for frequency domain analysis of a linear system between wind and wave from the full scale metocean data of three platforms located in different operating field. From here we are able to determine the correlation of these environmental forces to estimate the significance frequency where these forces acts in linear functions in the system, thus identify the response of the platform structural members as we assume the inputs to be stationary. It is very crucial to determine the response of the structural members so that we can improve the platform design standards and also as approaches to standard maintenance procedures. This project will focus on the metocean data collected from each platform for different field operation; Dulang-B platform from Peninsular Malaysia Operation (PMO), Tukau platform form Sarawak Operation (SWO) and Samarang platform from Sabah Operation (SBO). This is to ensure that we are able to distinguish the environmental condition for each set of metocean data as well as the seasonal pattern. The measured data is analyzed using the assistance of mathematical software, PASW 18 in order to compute the complex algorithm involved. The results obtained show that the wind is not actually the major factor to generate the wave at specific platforms. It is estimated up to 30% only while other factors that contribute to generate wave are possibly the tidal effect, gravity pull or other parts of the sea. The coherency differs for platform at different operation field region, as well as for seasonal pattern. The highest coherency recorded is the interaction of wind and waves at Tukau during non monsoon season, where the interaction of both forces optimum at frequency O.lHz, while other platforms show a true non linear relationship of wind and waves. However during monsoon season shows the other way around where Dulang-B platform and Samarang shows a quite similar seasonal pattern, but slightly differs in the coherency range.